2012
DOI: 10.1093/ajae/aar142
|View full text |Cite
|
Sign up to set email alerts
|

Investment in Cellulosic Biofuel Refineries: Do Waivable Biofuel Mandates Matter?

Abstract: A floor and trade policy in Renewable Identification Numbers (RINs) is the market mechanism by which U.S. biofuel consumption mandates are met. A conceptual model is developed to study the impact of RINs on stimulating investment in cellulosic biofuel refineries. In a two-period framework, we compare the first-period investment level (FIL) in three scenarios: (1)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…de Gorter and Just (2009), Lapan and Moschini (2012), and Holland et al (2009) study the market effects and efficiency of fuel mandates such as the RFS2 and California's Low Carbon Fuel Standard. More recent work compares welfare and markets outcomes under fuel mandates to those under taxes and cap and trade programs in alternative market settings and with different policy designs (Rajagopal et al, 2011;Rajagopal and Plevin, 2013;Lemoine, 2016;Bento et al, 2014;Lade and Lin Lawell, 2015a), explores unintended consequences of fuel mandates (Khanna et al, 2008;Holland et al, 2014Holland et al, , 2015, and studies the impact of economic and policy uncertainty on the incentive for investments in advanced fuel technologies (Miao et al, 2012;Clancy and Moschini, 2015). 5…”
Section: Previous Literaturementioning
confidence: 99%
“…de Gorter and Just (2009), Lapan and Moschini (2012), and Holland et al (2009) study the market effects and efficiency of fuel mandates such as the RFS2 and California's Low Carbon Fuel Standard. More recent work compares welfare and markets outcomes under fuel mandates to those under taxes and cap and trade programs in alternative market settings and with different policy designs (Rajagopal et al, 2011;Rajagopal and Plevin, 2013;Lemoine, 2016;Bento et al, 2014;Lade and Lin Lawell, 2015a), explores unintended consequences of fuel mandates (Khanna et al, 2008;Holland et al, 2014Holland et al, , 2015, and studies the impact of economic and policy uncertainty on the incentive for investments in advanced fuel technologies (Miao et al, 2012;Clancy and Moschini, 2015). 5…”
Section: Previous Literaturementioning
confidence: 99%
“…Dumortier et al [16] showed that the exercise of a cellulosic waiver would make landowners unwilling to switch from conventional crops to bioenergy crops, reducing cellulosic feedstock supply. Miao et al [17] found that a cellulosic waiver had no effect on investment decisions. They also found that, when firm-level marginal costs were not constant, higher RIN prices under a waivable mandate stimulated first stage investment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies have analyzed the impact of the RFS mandates on the production and consumption of renewable fuel, but most focused on corn-based ethanol and other firstgeneration biofuel feedstocks (e.g., Anderson and Coble, 2010;Gallagher et al, 2003;Gardner, 2007;Babcock, 2008a, 2008b;McCullough et al, 2011;McPhail, 2013, Chen andKhanna 2012). To date, only two studies, Miao et al (2012) and Chen and 4 Khanna (2012), examined how biofuel mandates affect the growth of the cellulosic biofuel industry. The most important of these for our purposes is Miao et al (2012), who modeled the impact of Renewable Identification Numbers (RINs) -tradable instruments developed by the EPA to implement EISA -on investments in cellulosic biofuel refineries given that the EPA is able to reduce the mandate from the original EISA level.…”
mentioning
confidence: 99%
“…To date, only two studies, Miao et al (2012) and Chen and 4 Khanna (2012), examined how biofuel mandates affect the growth of the cellulosic biofuel industry. The most important of these for our purposes is Miao et al (2012), who modeled the impact of Renewable Identification Numbers (RINs) -tradable instruments developed by the EPA to implement EISA -on investments in cellulosic biofuel refineries given that the EPA is able to reduce the mandate from the original EISA level. They concluded that a waivable mandate may induce investment if refinery-level marginal costs are increasing but it has no effect on investment level if marginal costs are constant.…”
mentioning
confidence: 99%
See 1 more Smart Citation